Respostas
respondido por:
5
Multiplique toda equação por 3 , para eliminar a fração 2/3
2z +3 = z + 2/3 (3)
6z + 9 = 3z + 2
6z - 3z = 2 - 9
3z = -7
z = -7 / 3
Resposta: z = -7/3
2z +3 = z + 2/3 (3)
6z + 9 = 3z + 2
6z - 3z = 2 - 9
3z = -7
z = -7 / 3
Resposta: z = -7/3
respondido por:
1
2z +3 =( 3z + 2)/3
3*(2z +3) = 3z + 2
6z + 9 = 3z + 2
6z - 3z =2-9
3z = -7
z = -7/3
solução = -7/3
att: Jhonny
3*(2z +3) = 3z + 2
6z + 9 = 3z + 2
6z - 3z =2-9
3z = -7
z = -7/3
solução = -7/3
att: Jhonny
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás